A Glucagonoma Presenting as Cerebral Vein Thrombosis and Diabetes. (22nd April 2022) - Delli Colli, Marina; Alamri, Bader N.; Palma, Laura; Rivera, Juan
Abstract : Glucagonomas are rare pancreatic neuroendocrine tumors (pNETs), malignant in 80% of cases, thus highlighting the importance of early diagnosis and treatment. Primary manifestations are diabetes, dermatosis, depression, weight loss, and deep vein thrombosis. Unlike other pNETs, glucagonomas are associated with a higher incidence of thromboembolic events, often resulting in death. We present the case of a glucagonoma patient whose primary manifestation was cerebral sinus venous thrombosis (CS-VT). Early diagnosis enabled curative resection. The purpose of this paper is to review the underlying mechanisms associated with increased coagulopathy in glucagonomas.